METHODOLOGY OF TEACHING MUSIC IN THE MIDDLE CLASS (Conferencea, 2022)
This article provides detailed information on how music teachers can increase students’ interest in music lessons through a variety of methods, how to use visual methods in music lessons, and how to sing songs.